Enrollment and retention of female sex workers in HIV care in health facilities in Mbarara city - Arinaitwe, Bridget; Ariho, Philbert; Naturinda, Christine Hilda; Byoleko, Brian; Base, Anitah; Atwijukiire, Humphrey; Matavu, Hariat; Kabami, Jane; Obua, Celestine; Wakida, Edith K.; Otwine, Anne (Frontiers in Reproductive Health, 2023)
Background Sex work is a global driver of the HIV epidemic, and the risk of acquiring HIV is 13 times higher for female sex workers (FSWs) compared to the general population. The enrollment and retention of FSWs in HIV care is a challenge and has been a major contributing factor to increased new HIV infections. Methods We conducted a qualitative study among 30 FSWs and 21 healthcare workers (HCWs) working in antiretroviral therapy (ART) clinics at the selected three primary health facilities in Mbarara City, Southwestern Uganda. The study participants were enrolled by both purposive and snowball sampling techniques. We obtained informed consent from all the participants, and data were collected using in-depth interviews and thematically analyzed. Results Three themes emerged as facilitators toward enrollment and retention of FSWs into HIV care, namely, (1) good health living, (2) receptive HCWs and availability of health services, and (3) community outreach services and peer support. The barriers are summarized into four major themes: (1) stigma, community discrimination, and beliefs; (2) social obstacles; (3) adverse effects of ART; and (4) inadequate services at the health facilities. Conclusion FSWs are challenged by unsupportive environments and communities where they live and work, which hinders their enrollment and retention in HIV care. Creating awareness of the utilization of HIV care services and extending such services to hotspot communities could enhance the response of HIV-positive FSWs to ART.